2017
DOI: 10.1002/aur.1749
|View full text |Cite
|
Sign up to set email alerts
|

Binocular rivalry in children on the autism spectrum

Abstract: When different images are presented to the eyes, the brain is faced with ambiguity, causing perceptual bistability: visual perception continuously alternates between the monocular images, a phenomenon called binocular rivalry. Many models of rivalry suggest that its temporal dynamics depend on mutual inhibition among neurons representing competing images. These models predict that rivalry should be different in autism, which has been proposed to present an atypical ratio of excitation and inhibition [the E/I i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
2
21
1
Order By: Relevance
“…In a recent study, Karaminis et al investigated binocular rivalry in ASD. Binocular rivalry occurs when the two eyes are presented with images that are not compatible, and to avoid confusion of this percept, visual perception oscillates between the two images from each eye, and may amalgamate for brief periods of time.…”
Section: Stereopsis and Oculomotor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Karaminis et al investigated binocular rivalry in ASD. Binocular rivalry occurs when the two eyes are presented with images that are not compatible, and to avoid confusion of this percept, visual perception oscillates between the two images from each eye, and may amalgamate for brief periods of time.…”
Section: Stereopsis and Oculomotor Functionmentioning
confidence: 99%
“…Inhibition of visual information is required for binocular rivalry to occur, and some studies have reported that cortical inhibition is atypical in ASD, due to altered release and signalling of excitatory and inhibitory neurotransmitters . Therefore Karaminis et al hypothesised that if there were an imbalance in the excitation/inhibition neural mechanisms in ASD, then binocular rivalry would be altered. They investigated this in 16 children with ASD aged 7–14 years and typically developing age‐ and IQ‐matched controls and reported that while there was no difference in the number of transitions of fixation between the ASD and control participants, children with ASD showed shorter durations of mixed percepts.…”
Section: Stereopsis and Oculomotor Functionmentioning
confidence: 99%
“…Because mixed percepts have such a high likelihood in the fovea, an understanding of dominance effects in this area must include an examination of the mixed report as well. Indeed, recent studies have suggested that the mixed percept is itself worthy of investigation, with this phase of rivalry being highlighted as being uniquely altered within clinical populations [27][28][29][30] and correlated with certain personality traits [31]. In the current study, therefore, we will track such percepts and include them in an understanding of onset dominance in rivalry.…”
Section: Introductionmentioning
confidence: 98%
“…Following Pettigrew and Miller's [68] original study on BD, other clinical psychiatric conditions have been examined including schizophrenia and major depression [39,53], autism spectrum conditions [4,26,42,[71][72][73], attention deficit hyperactivity disorder (e.g., [3,6]), and generalized social anxiety disorder [5]. Although some researchers (e.g., [82]) have attempted to use the same testing protocol as that of Pettigrew and Miller [68], so that data may be directly compared between clinical studies, other researchers have employed different test protocols (e.g., shorter viewing durations, different stimulus characteristics, different response options), making comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%